ÇOCUK CERRAHİSİNDE MEKANİK VENTİLASYON UYGULAMALARI - İLÇE, Zekeriya; AKOVA, Fatih; ERAY, Nur; CELAYİR, Sinan (Cerrahpaşa Medical Journal, 2019)
Background.- Neonatal surgical mortality has decreased with the establishment of neonatal intensive care units (NICU) and mechanical ventilation (MV). The main indications for MV in the NICU patients are immaturity of lungs in preterm newborns and congenital or acquired lung infections. Congenital diaphragmatic hernia (CDH), abdominal wall defects, esophageal atresia and congenital gastrointestinal anomalies are major surgical indications for MV in NICU patients. The aim of this study was to determine the results of MV treatment and discuss the role of pediatric surgical team in such cases. Design.- A retrospective analysis of all consecutive admissions to pediatric surgical neonatal intensive care unit was performed five years (1995-1999). The cases that underwent MV were examined for age, gender, duration of hospitalization, medications, indications, yearly distribution and mortality. Results.- In this study 489 newborn were evaluated. The mean birth weight and the mean age of infants were 2750g and 3,5 days respectively. The male: Female ratio was 2:1. Total 166 neonates (34%) were mechanically ventilated. The most common indication for the MV was CDH (77.1%). The overall mortality in mechanical ventilated patients was 53,6%, however this rate decreased in recent years. The most frequent reason for the mortality was CDH (62,2%). Conclusion.- MV of newborns is a complex and invasive procedure. In our country most of, the pediatricians are not familiar with neonatal pediatric surgical problems due to the deficiency in the numbers of children hospitals. Therefore many pediatric surgeons should handle MV in their own departments. In conclusion, this study shows the improvement in the results of MV, by the increasing experience and improved training programs MV pediatric surgical NICU.